The Impact of Business Diversification on Performance of IDX Listed Firms - Humarseno, Ony; Chalid, Dony Abdul (UI Scholars Hub, 2013)
This study analyzes the correlation between business diversification and performances in Indonesian listed companies from 2006-2011. In addition to observing business diversification impact on company’s performance in term of Return on Assets (ROA) and Tobin’s Q, this research also observes the business diversification impact on the performances of different companies at different level. The result of this research indicates that diversification gives negative effect to ROA and Tobin’s Q, while for higher level of diversification, the effect on Tobin’s Q is relatively high. The negative effect of diversification on ROA is higher in the group of companies with higher ROA. The different results show that when using Tobin’s Q as a measure of companies’ performances, diversification gives negative impact to companies’ performance in the intermediate level.